PENGARUH GOOD CORPORATE GOVERNANCETERHADAP KINERJA PERUSAHAAN: Studi pada Perusahaan Sektor Indus tri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2019 (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
This study aims to analyze "THE EFFECT OF GOOD CORPORATE GOVERNANCE ON COMPANY PERFORMANCE (Study on Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period)". By using our mechanisms of Good Corporate Governance, namely the Board of Directors, Board of Commissioners, Managerial Ownership, and Institutional Ownership as independent variables, while company performance is measured using Return On Assets (ROA) as the dependent variable. This study uses quantitative data with secondary data sources. Research data collection techniques using literature and documentation. The population in this study were 52 companies listed on the Indonesia Stock Exchange in the Consumer Goods Industry Sector. The research sample used a purposive technique with a total of 10 companies that met the characteristics. This study uses data analysis methods, namely: classical assumptions, multicollinearity, autocorrelation, heteroscedasticity, multiple correlation, multiple regression, coefficient of determination, t and F tests. (2 tailed) = 0.177> 0.05, meaning that there is no significant effect between the Board of Directors and company performance. H2 T test results obtained values -2.386 <1.70814 and Sig. (2tailed) = 0.025 <0.05, meaning that the Board of Commissioners has a significant effect on company performance. The results of the T H3 test obtained the results of -1.189 <1.70814 and Sig. (2 tailed) = 0.246> 0.05, it means that Managerial Ownership has no significant effect on company performance. The results of the T H4 test showed the results of 2.943> 1.70814 and Sig. (2 tailed) = 0.007 <0.05, meaning that institutional ownership has a significant effect on company performance. From the results of the F test, it is found that the calculated F value is greater than the F table (3.405> 2.60), and the calculated significant value is smaller than the predetermined significant value (0.024 <0.05), which means the variables of Directors, Board of Commissioners, Managerial Ownership and Institutional Ownership have a significant effect on company performance.